Modular Autonomous Robotics Platform for Educational Use - Ortega-Sanchez, Cesar; Lumsden, J. (IEEE, 2010)
Robotics is a field that continues to grow as robots become common in environments as varied as households and the battlefield. This paper presents a low cost robotics development platform using commercial off-the-shelf parts for educational and academic use. It is a direct response to the high cost and limited functionality of existing platforms. A navigation and obstacle-avoidance Fuzzy Controller is provided to accelerate the typical development process for a mobile robot. The fundamental aim is to facilitate future robotics projects by producing an inexpensive, modular and highly accessible platform that improves upon existing commercial offerings.